Analisis Profitabilitas dengan Penyaluran Kredit Sebagai Variabel Intervening pada Perusahaan Perbankan di Bursa Efek Indonesia - Titian Rendra Hadianto; Tri Kartika Pertiwi (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2021)
This research aims to determine the profitability of banks which is influenced by several factors. While this research uses purposive sampling with the analysis technique of Statistical Package for the Social Sciens and Path Analysis. The results of this study conclude: Capital Adequacy Ratio has a negative contribution to the level of bank profitability. The ratio of third party funds has a contribution to the level of bank profitability. Capital Adequacy Ratio has a negative contribution to Banking Credit Distribution (LDR, Third Party Funds Ratio (TPF) has a contribution to Banking Credit Distribution. Capital Adequacy Ratio has a contribution to the level of Banking Profitability by Lending as Intervening. Third Party Funds Ratio has a contribution to the level of Banking Profitability by Lending as Intervening Credit has a negative contribution to the level of bank profitability.